The effects of language teachers’ attitudes, barriers and enablers in teaching 21st century skills at Chinese vernacular schools - Abdullah, Melissa Ng Lee Yen; Tiew, Chia Chun (Universiti Utara Malaysia Press, 2022)
Purpose – The study explored the barriers and enablers faced by language teachers in teaching 21st century skills at Chinese vernacular schools. It aimed to determine the effects of teachers’ attitudes, barriers, and enablers in teaching the skills during language lessons.